Standardization of collection methods, nutritional evaluation, and estimation of microbial load of the Gobhakshita Yava (Cow Fed Pre-Digested Barley) and Gobhakshita Godhuma (Cow Fed Pre-Digested Wheat) - Seema Harshadbhai Kathavadiya; Rabinarayan Acharya (Wolters Kluwer Medknow Publications, 2023)
Introduction: In Ayurveda, to treat Prameha, various eatables prepared from the barley (Yava) or bamboo seeds (Venuyava) or wheat (Godhuma), previously eaten either by donkey, or horses, or cows, or swans and or deer, being collected from their dung are recommended. The present article details the method of collection, quality and the outcome of two commonly used cereals barley and wheat. Methods: The present study was carried out on 12 Geer cows (six were fed barley and six wheat), 1.5 kg grains per day per cow for 3 days in three different seasons, i.e., monsoon (Varsha ritu), winter (Hemant ritu), and summer (Vasanta ritu). The cow dung was collected throughout the day and thoroughly washed two to three times with tap water, and obtained barley and wheat were dried under direct sunlight. The input and outcome of the Gobhakshita yava (cow-fed predigested barley) and Gobhakshita godhuma (cow-fed predigested wheat) were estimated. Then, the samples were analyzed for nutritional values and microbial contaminations. Results: In the monsoon, winter and summer season, the percentage yield of Gobhakshita yava was 28.44%, 32.22%, 42.59%, and Gobhakshita godhuma was 29.44%, 33.77%, and 44.44%, respectively. Total soluble sugar was reduced in all Gobhakshita yava samples. In Gobhakshita godhuma, total fat, total soluble sugar, total protein, and total starch were decreased. Microbial contamination was noticed in monsoon and winter seasons samples, whereas the summer samples were devoid of any microbial growth. Conclusion: The summer season was found to provide more yield and no microbial growth in both Yava and Godhuma samples. Both Gobhakishita Yava and Godhuma contain lower total soluble sugar in comparison to their raw samples.